2018
DOI: 10.1039/c7cc08885j
|View full text |Cite
|
Sign up to set email alerts
|

Observation of polar order and thermochromic behaviour in a chiral bent-core system exhibiting exotic mesophases due to superstructural frustration

Abstract: A new approach accompanied by superstructural frustration is reported. By attaching a cholesterol moiety directly to the central bent-core system it displayed exotic BPIII, BPII/I, Ncyb*, TGBA, SmAPA, SmA and SmX phases as shown by X-ray scattering results. While higher homologues of the series exhibited spontaneous formation of polar order (Ps ∼ 61 nC cm-2) upon applied voltage, the lower homologues showed thermochromic behaviour which can also be trapped via temperature quenching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Othert han these major differences, the two molecules had differencesi no ther bond angles and torsion angles of AD FT study was performed on compound 1-4 (as ar epresentativec ase) and an analogous compound with am ethyl core reported earlier. [47] It was found that the dipole moment along the y direction( Figure S40 and Ta bles S6 and S7 in the Supporting Information) was much larger (m y = 2.55 D) in compound 1-4 than that in the previously reported molecule (m y = 1.272 D), although the dipole moments along the other two directions (x and z)r emained similari nb oth compounds. This observation implies that the introduction of the ÀCl moiety in the kink direction of the molecule (Figure 2a)e lectronically affects nucleation of the usual mesophases (e.g.,n ematic or Sm) and stabilizes the frustrated BPs.…”
Section: Single-crystal X-ray Diffraction (Scxrd) Studiesmentioning
confidence: 63%
See 4 more Smart Citations
“…Othert han these major differences, the two molecules had differencesi no ther bond angles and torsion angles of AD FT study was performed on compound 1-4 (as ar epresentativec ase) and an analogous compound with am ethyl core reported earlier. [47] It was found that the dipole moment along the y direction( Figure S40 and Ta bles S6 and S7 in the Supporting Information) was much larger (m y = 2.55 D) in compound 1-4 than that in the previously reported molecule (m y = 1.272 D), although the dipole moments along the other two directions (x and z)r emained similari nb oth compounds. This observation implies that the introduction of the ÀCl moiety in the kink direction of the molecule (Figure 2a)e lectronically affects nucleation of the usual mesophases (e.g.,n ematic or Sm) and stabilizes the frustrated BPs.…”
Section: Single-crystal X-ray Diffraction (Scxrd) Studiesmentioning
confidence: 63%
“…[43][44][45] Therefore, the salicylideneaniline and cholesterol units play an important role in the mechanochromic behavior of this class of compounds. [43][44][45][46] In our previous report, [47] we showedt hat 3-amino-2-methylbenzoica cid (as the central core, [47-49, 52, 53, 55] Figure 1a)b ased smartb ent-core materials exhibited frustrated structures that stabilized BPs for about 2.0 8C and the TGB phase fora bout 31.0 8C. The direct attachment of the cholesterol moiety to the central core, functioning as an arm of the BCLC (Figure 1), promotes rigidness in the molecular architecture, which eventually leads to the realization of different frustrated phases.T he methyl group (ÀCH 3 ), with the + I effect and its bulky size (relative to H), widened the bent angle and supported the stabilization of different phase structures.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations